(untitled) (Plant Tissue Culture and Biotechnology, 2023)
Antibiotic resistant E. coli in the animal gut can promote the transfer of antibiotic resistance between animal and human. In order to enforce the National Action Plan in Bangladesh, it is imperative to detect the presence of E. coli harbouring Class 1 integrons that can potentially transfer antibiotic resistance genes among bacteria. Previously used primers pairs were used in a multiplex PCR to successfully detect the E. coli species-specific amplicon and Class 1 integron in 57% of the isolates. Plasmid was absent in the isolates. Antibiotic resistance profiling indicated highest resistance to oxytetracycline (89%) and lowest resistance to streptomycin (18.52%). A total of 38% isolates were found to be resistant against 8 of the 10 antibiotics used, 85.19% being multidrug resistant. However, the resistance pattern could not be specifically correlated to the presence of Class 1 integron. The validated multiplex PCR can be used as a quick method to detect E. coli and Class 1 integron simultaneously. Plant Tissue Cult. & Biotech. 33(1): 17-24, 2023 (June)